The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3945/ajcn.112.046961
|View full text |Cite|
|
Sign up to set email alerts
|

Lack of a relation between serum 25-hydroxyvitamin D concentrations and asthma in adolescents

Abstract: In 2 samples of adolescents, overall serum 25(OH)D concentrations were low and were not consistently associated with the presence of asthma, multiple asthma characteristics, asthma morbidity, or response to treatment. The ACE trial was registered at clinicaltrials.gov as NCT0011441.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 29 publications
2
48
1
1
Order By: Relevance
“…In a study, the frequency of vitamin D deficiency (54%) or insufficiency (86%) in 92 African-American asthmatic children aged 6-20 years was found to be higher than in healthy controls (18). However, there are other studies that did not find a difference in Vitamin D levels between patients with and without asthma (8,(13)(14)(15). In accordance with these reports, serum vitamin D levels were similar in patients with and without asthma in our study.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In a study, the frequency of vitamin D deficiency (54%) or insufficiency (86%) in 92 African-American asthmatic children aged 6-20 years was found to be higher than in healthy controls (18). However, there are other studies that did not find a difference in Vitamin D levels between patients with and without asthma (8,(13)(14)(15). In accordance with these reports, serum vitamin D levels were similar in patients with and without asthma in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Gergen et al reported the absence of a relationship between vitamin D levels and severity of asthma among adolescents (14). Serum vitamin D levels of the patients and control group in that report was under 20 ng/ml, as was the case in our study.…”
mentioning
confidence: 37%
See 2 more Smart Citations
“…Bazı kesitsel çalışmalarda serum D vitamini düzeylerinin astımlı çocuklarda sağlıklı çocuklara göre daha düşük olduğu (4,(10)(11)(12) sınırlı sayıdaki çalışmada serum D vitamini düzeylerindeki yüksekliğinin astım riskinde artmaya neden olduğu gösterilmiştir (13,14). Bazı çalışmalarda ise bu farklılıklar gözlenmemiştir (15)(16)(17)(18)(19). D vitamini ve günümüzdeki astım rehberlerinde astım tedavisinin ana amacı olarak ifade edilen astım kontrolü ilişkili yapılmış sınırlı sayıda çalışma vardır.…”
Section: Introductionunclassified